Determination of selected heavy metals in street food around Jengka area / Wan Noni Afida Ab Manan, Nik Nur Syafiqa Nik Hashim and Nur Sha'adah Zainuddin - Ab Manan, Wan Noni Afida; Nik Hashim, Nik Nur Syafiqa; Zainuddin, Nur Sha'adah (Universiti Teknologi MARA Cawangan Pahang, 2019)
High consumption of street food may cause harmful health effects due to contamination of heavy metal. Two items of street food, namely: i)fried banana and, ii)Keropok Lekor were collected from stalls nearby Bandar Pusat Jengka area to determine and compare selected metals (Al, Cd, Cu and Pb) concentrations to the permissible limit set by Food and Agriculture Organization (FAO) and World Health Organization (WHO). Both fried banana and Keropok Lekor samples were prepared by wet digestion using amixture of HNO3and H2O2. These prepared samples were then analysed using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES). All concentrations of selected metals were below the maximum standard set by FAO/WHO. The highest concentration for Al, Cd, Cu and Pb in both samples were 0.270mg/kg, 0.093 mg/kg, 0.077mg/kg and 0.327mg/kg, respectively. In comparison with its permissible limit, all samples did not exceed the limits which are Al (1 mg/kg), Cd (0.2 mg/kg), Cu (2.0 mg/kg) and Pb (0.5 mg/kg) for fruit and Al (1 mg/kg), Cd (0.5 mg/kg), Cu (3 mg/kg) and Pb (0.5 mg/kg) for fish.Nevertheless, it should be noted that consuming the street food for a long time with excess amount may contribute to health effects.